Західнополіські неофіційні антропоніми, утворені лексико-семантичним способом - Шульська, Наталія Миколаївна; Shulska, Nataliуa (Східноєвропейський національний університет, 2013)
У статті проаналізовано прізвиська жителів Західного Полісся, утворені лексико-семантичним способом. Охарактеризовано неофіційні найменування людей, твірною базою яких послугували апелятиви розрядів «nomina personalia» і «nomina impersonalia». Серед фактажу західнополіських неофіційних іменувань засвідчено такі групи апелятивів: назви-характеристики за зовнішнім виглядом особи, внутрішнім світом людини, родом заняття чи процесуальною дією, за специфікою мовлення; національною чи територіальною ознакою, родинними стосунками. З’ясовано також суть подвійної семантизації у вуличних антропонімах, семантизації композитів і словоскладних форм, словосполучень. The article analyzes the nicknames of inhabitants Western Polissya, formed lexical-semantic method. Characteristic of nicknames, traces of which served as a base apelyativs bits «nomina personalia» and «nomina impersonalia». When semantyzation nickname installed in their original appeal by origin, attested in the literary language or dialect, otherwise – the so-called «situational» or analohiyni apelyativs. Among nicknames of Western Polissya witnessed such groups apelyativs: names, features the appearance of the person's inner world of man, a native classes or remedial action for the specific language, ethnic or territorial basis, and family relationships. In the category of personal naming «nomina impersonalia» analyzed nickname derived from fauna and flora, names realities of economic life, anatomical and abstract names. We show also dual core semantyzatsiyi in nicknames, semantyzations composites and word-bilding forms phrases.
The Nicknames of Inhabitions of Western Polissya that Emerged Lexical-semantic Method
Keywords: неофіційна антропонімія; прізвисько; Західне Полісся; лексико-семантичні утворення; апелятив; лексико-тематична група